Interaction of Climate Change and Green Stocks on Economic Growth in ASEAN-5 - Amalia, Sopira Qori; Suriani, Suriani (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: This study presents a new interaction of climate change in moderating the effect of green stocks, exchange rates, and net exports on economic growth in ASEAN-5 countries. Research Objectives: This study aims to analyze the interaction of climate change on green stocks, exchange rates, and net exports on economic growth in ASEAN-5 countries. Research Methods: This study used quarterly panel data from ASEAN-5 countries, 2016-2022, and selected a fixed effects model as the best model. The moderated regression analysis (MRA) approach supports this research.Empirical Results: The results showed that green stocks, exchange rates, and net exports positively affect economic growth in ASEAN-5 countries. The interaction of climate change on green stocks and exchange rates has a negative effect on economic growth. However, the interaction of climate change on net exports positively affects economic growth in ASEAN-5 countries. It represents that climate change can weaken the effect of green stocks and exchange rates on economic growth. Meanwhile, climate change can strengthen the effect of net exports on economic growth in ASEAN-5 countries. Implications: This study implies that the government needs to increase investment in green stocks to support financing that can mitigate climate change and develop net exports to increase economic growth toward a green economy. Similarly, the ASEAN-5 central banks, as monetary authorities, can maintain exchange rate fluctuations to achieve stable economic growth.JEL Classification: F31, F43, G11, Q54, Q56